Returned : Going and Coming in an Age of Deportation - Boehm, Deborah A. (Book collections on Project MUSE., 2016)
"This book follows transnational Mexicans as they experience the alienation and unpredictability of deportation, tracing the particular ways that U.S. immigration policies and state removals affect families. Deportation--an emergent global order of social injustice--reaches far beyond the individual deportee, as family members with diverse U.S. immigration statuses, including U.S. citizens, also return after deportation or migrate for the first time. RETURNED tells the story of the chaos, and design, of deportation and its aftermath."--Provided by publisher